Maturity‐onset diabetes of the young type 5 in a family with diabetes and mild kidney disease diagnosed by whole exome sequencing. Issue 11 (November 2014) - Wentworth, J. M.; Lukic, V.; Bahlo, M.; Finlay, M.; Nguyen, C.; Morahan, G.; Harrison, L. C.
Abstract: Exome sequencing is being increasingly used to identify disease‐associated gene mutations. We used whole exome sequencing to determine the genetic basis of a syndrome of diabetes and renal disease affecting a mother and her son. We identified a mutation in the hepatocyte nuclear factor 1‐b ( HNF1B ) gene that encoded a methionine to valine amino acid change (M160V) in the HNF1B protein. This leads us to the previously unappreciated diagnosis of maturity‐onset diabetes of the young type 5 and provided a basis for genetic counselling of other family members.